Anxiety, Depression and Quality of Life of Parents in Cerebral Palsy Treatment - Lorena Mirele Pereira; Marina Kohlsdorf (Interação em Psicologia, 2014)
The cerebral palsy is a sensorial and motor dysfunction that demands from parents intense care related to the child. This paper had the main goal of evaluating depression, anxiety and quality of life in 27 parents of children with cerebral palsy. Two questionnaires were included (Beck Anxiety Inventory and Beck Depression Inventory), besides a semi-structured interview. Results show that 18 parents reported minimum anxiety and depression was verified in ten participants. Interviews highlighted difficulties related to financial and professional issues as a relevant moderator in treatment adaptation. Actions related to public health care are necessary in order to minimize operational costs and financial difficulties associated to cerebral palsy treatment.